2007
DOI: 10.1103/physrevlett.98.081802
|View full text |Cite
|
Sign up to set email alerts
|

Does the HyperCP Evidence for the DecayΣ+pμ+μIndicate a Light Pseudoscalar Higgs Boson?

Abstract: The HyperCP Collaboration has observed three events for the decay Sigma+ -->p mu+mu- which may be interpreted as a new particle of mass 214.3 MeV. However, existing data from kaon and B-meson decays provide stringent constraints on the construction of models that support this interpretation. In this Letter we show that the "HyperCP particle" can be identified with the light pseudoscalar Higgs boson in the next-to-minimal supersymmetric standard model, the A10. In this model there are regions of parameter space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
80
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 23 publications
2
80
0
Order By: Relevance
“…To this end, various ideas have been proposed in the literature [8,9]. Specifically, we have demonstrated that a light pseudoscalar Higgs boson in the next-to-minimal supersymmetric standard model (NMSSM), the A 0 1 , could be identified as the possible new particle responsible for the HyperCP events while satisfying all constraints from kaon and B-meson decays [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To this end, various ideas have been proposed in the literature [8,9]. Specifically, we have demonstrated that a light pseudoscalar Higgs boson in the next-to-minimal supersymmetric standard model (NMSSM), the A 0 1 , could be identified as the possible new particle responsible for the HyperCP events while satisfying all constraints from kaon and B-meson decays [9].…”
Section: Introductionmentioning
confidence: 99%
“…Here we consider not only the charginomediated diagrams of Refs. [9,14], but also the gluino-and neutralino-mediated diagrams discussed in Ref. [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulated by this exciting new discovery, some important literatures on interpreting and finding this new particle came out: Gorbunov and Rubakov suggested [2] that Sgoldino -superpartner of goldino -may take the responsibility for the anomalous events mentioned above; X.-G. He and his colleague [3] argued that this new "HyperCP particle" can be identified with the light pseudoscalar Higgs boson in the next-to-minimal supersymmetric standard model. The most recent effort in finding this novel particle X was done by Tung et al…”
mentioning
confidence: 99%